1996
DOI: 10.1155/1996/240781
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Extracorporeal Shock Wave Lithotripsy of Pancreatic Ductal Stones: Six Years’ Experience

Abstract: Extracorporeal shock wave lithotripsy (ESWL) and endoscopic sphincterotomy (EST) was performed in 35 patients suffering from pancreatic duct stones. Calculi disintegration and resolution of obstruction were achieved in all cases. Completely stone-free ducts were achieved in 16 patients (46%) while some peripheral asymptomatic stone material remained in 19 (54%). Dilation of the main pancreatic duct was reduced in 29 patients (83%). Twelve patients (34%) became completely asymptomatic and 17 (49%) reported a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Pancreatitis and especially severe pancreatitis is a rare complication of ESWL therapy to the pancreas [1, 7, 8, 9]. Mild pancreatitis or hyperamylasemia is reported in approximately 4% of pancreatic duct calculi treated by ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatitis and especially severe pancreatitis is a rare complication of ESWL therapy to the pancreas [1, 7, 8, 9]. Mild pancreatitis or hyperamylasemia is reported in approximately 4% of pancreatic duct calculi treated by ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…ESWL is required in 36−68% of patients and successful rates of stone clearance of the main pancreatic duct ranged from 37% to 100% [115,120,173,[179][180][181][182][183][184][185][186][187]. Use of ultrasound instead of x-rays to locate pancreatic stones is associated with a lower fragmentation rate [188,189]. Data regarding mechanical or intraductal lithotripsy technique are limited and showed it to be technically challenging, cumbersome and requiring highly specialized equipment [190,191].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…Complete stone clearance rates vary between 39 and 76%, but complete stone clearance is probably not always required for symptom relief [25,30,31,32,35,37,38,39,40,41,42,43,44,45]. Dumonceau et al [46 ]reported a significant association between immediate disappearance of pain and complete or partial PD clearance.…”
Section: Endoscopic Therapymentioning
confidence: 99%
“…The mean effect size (weighted correlation coefficient) was 0.62 for pain and 0.74 for duct clearance [47]. A complete or partial pain relief of 48-91% has been found in patients who underwent ESWL and endoscopy during a follow-up ranging from 6 to 77 months [30,31,32,34,35,37,38,39,40,41,42,43,44,45,46]. Usually, an immediate relief of pain is associated with successful decompression of the main PD (as suggested by decrease in its diameter or stone clearance) [32,35,43,46].…”
Section: Endoscopic Therapymentioning
confidence: 99%